Peak To Average Power Ratio Reduction In Wireless Orthogonal Frequency Division Multiplexing - Wahab, Aeizaal Azman Abdul (2014)
Orthogonal Frequency Division Multiplexing (OFDM) offers an attractive multicarrier technique with high spectral efficiency, simple implementation and robustness against multipath fading. A trend of OFDM development is to increase the number of subcarriers to enhance efficiency. However, when the number of subcarriers increases, certain time domain OFDM coefficients are likely to acquire excessively large magnitudes. As such, the OFDM baseband waveform is susceptible to high PAPR value and may suffer from non linear distortion at subsequent power amplifier stage. This high PAPR can limit the transmitter power efficiency, cause spectral spreading and reduce the bit-error-rate (BER) performance. To alleviate these potential performance problems, two novel computationally efficient and low cost PAPR reduction methods are proposed. The first method, called DCT-OFDM Method, seeks to apply alternative structure for transmitting the high speed data in the OFDM system. The character of the DCT energy focused is made use of in the frequency domain and it helps to reduce the PAPR engendered by IFFT at the transmitter statistically, avoiding the nonlinear distortion in OFDM systems due to great change of PAPR. It is mathematically verified that this method is potent to reduce PAPR. Simulation results show that about 2.2 dB reduction in PAPR value is achieved by this technique. Statistical Redistribution Method (SRM) which makes use of a non linear companding operation is selected and applied on the OFDM outputs signals has been used as a combination with Selected Mapping Method (SLM). The proposed scheme utilizes Selected Mapping (SLM) followed by the companding SRM technique to further reduce the PAPR of the OFDM signal. Simulation results indicate that about 5 dB reduction in PAPR is achieved compared with the conventional SLM algorithm.